IMPLICATIONS OF FULFILLING ANIMAL WELFARE AND ANIMAL PROTECTION DUE TO SPECIESIST AND ANTHROPOCENTRIC BELIEFS - Berandhini, Fiolita (Buletin Veteriner Udayana, 2023)
Every year, billions of animals are slaughtered on industrial agricultures and animals whose status does not include under the category of protected animals and stray dogs or cats are subjected to various kinds of abusive behavior by human as a result of the moral exclusion of animals of certain species. The idea of speciesism and anthropocentrism causes suffering on a massive scale that people may find hard to fathom. This paper discusses the definition of speciesism, anthropocentrism and its impact on advocacy for farm animals, stray animals and wild animals that are not protected by law, which begins with an explanation of how animals stand before the law and how society practices the concept of speciesism and anthropocentrism which has an impact on animal welfare. Then, identify how speciesism and anthropocentrism affects the protection of animals classified in certain species as a result of unfavorable protection or treatment for the animals. The position of animals that are still categorized as property by the law makes it difficult to apply animal protection for certain species of animals and for them who do not have owners. This condition occurs because the definitions of animals included in various existing laws are not in line with the clauses in the articles that should protect certain animal species as stated in the definitions in the regulations. In addition, there is a strong belief that certain species of animals such as the wildlife animals which are legally protected, companion animals (i.e. dogs and cats) and animals whose owned by people are more deserving of protection than other animal species and for non-owned animals. At the end of writing, this paper examines how the concepts of speciesism and anthropocentrism, which are unfavorable treatment or consideration towards those who are not categorized as the human and towards certain animal species which often become victims of speciesist and anthropocentric ideas have an impact on animal law protection.